Rasio aktivitas dan profitabilitas terhadap pertumbuhan laba pada perusahaan food and beverages - Leman, Eduardo Juan; Arisman, Anton (Journal of Accounting and Digital Finance, 2024)
Financial ratios are decisions for entities to help companies see whether their operational activities can continue to run. This analysis aims to determine the effect of Inventory Turnover, Net Profit Margin, and Return on Working Capital on the Profit Growth of Food and Beverage companies listed on the IDX in 2020-2023. The research method used in this study is a quantitative method with data in the form of secondary data, and the type of sample used is purposive sampling, which can produce the previous 33 samples multiplied by 4 years, namely 132 samples to become 44 samples. The analysis method used is multiple linear regression analysis, which has three independent and one dependent variable. The results of the hypothesis illustrate that Inventory Turnover has no effect on Profit Growth, Net Profit Margin has no impact on Profit Growth, and return on Working Capital has no effect on Profit Growth. The influence of the variables in this study on profit growth is 98.8 percent, and the rest is influenced by other variables outside of this hypothesis testing.